Pelaksanaan Jaminan Kesehatan Oleh BPJS Kesehatan Dalam Perspektif Syariah - Iwan Subandi; Fathurrahman Djamil (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2017)
Health is the basic right for everybody, therefore every citizen is entitled to get the health care. In enforcing the regulation for Jaringan Kesehatan Nasional (National Health Supports), it is heavily influenced by the foreign interests. Economically, this program does not reduce the people’s burdens, on the contrary, it will increase them. This means the health supports in which should place the government as the guarantor of the public health, but the people themselves that should pay for the health care. In the realization of the health support the are elements against the Syariah principles. Indonesian Muslim Religious Leaders (MUI) only say that the BPJS Kesehatan (Sosial Support Institution for Health) does not conform with the syariah. The society is asked to register and continue the participation in the program of Social Supports Institution for Health. The best solution is to enforce the mechanism which is in accordance with the syariah principles. The establishment of BPJS based on syariah has to be carried out in cooperation from the elements of Social Supports Institution (BPJS), Indonesian Muslim Religious (MUI), Financial Institution Authorities, National Social Supports Council, Ministry of Health, and Ministry of Finance. Accordingly, the Social Supports Institution for Helath (BPJS Kesehatan) based on syariah principles could be obtained and could became the solution of the polemics in the society.